Analisis Pelayanan Pajak Dalam Meningkatan Pendapatan Asli Daerah (PAD) Di Wilayah Kota Jakarta Utara - Featy Octaviany; Agung Edi Rustanto; Iis Kartini (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Each region has revenue that is used to carry out all activities in the region. The biggest source of income for a region comes from local taxes, one of which is hotel taxes. Local governments get local revenue from various types of local taxes. One of the local taxes that has considerable potential is hotel taxes. Local revenue through hotel taxes can continue to increase due to good tax services by the government to the hotel. Good service will make hotel tax payments run smoothly so that it can increase local revenue. This study aims to analyze the effect of tax services on increasing local revenue in North Jakarta. The research method used in this research is descriptive research with a qualitative approach. The data source used is primary data collected through direct distribution of questionnaires to hotels in the North Jakarta area, while secondary data used are the results of interviews, observations and documents related to hotel tax reports for the last 5 years. Based on the results of this study, it shows that the tax services provided by the Regional Income Agency (Bapenda) have a positive effect of 27.5%, but the effect is not significant. In this study, the form of tax services provided to the hotel includes reliability, responsiveness. assurance, emphaty, tangibles.